ANALISIS KOORDINASI TERHADAP PROGRAM K3 DAN IMPLIKASINYA PADA PRODUKTIVITAS KERJA KARYAWAN (Studi Kasus Pada Bagian Produksi di CV. Venus Inti Perkasa Pangkalpinang) - Ervandi, Rio; Prima Nugroho, Stefanus; Hariyani (Jurnal Progresif Manajemen Bisnis, 2018)
The purpose of this study is to determine the effect of coordination on safety, health and work welfare. This study also aims to examine the effect of safety, health and work welfare on work productivity, either partially or simultaneously. Theories used in this study are Management theory, Human Resource Management theory, Coordination theory, Occupational Safety theory, Occupational Health theory, Work Welfare theory and Work Productivity theory. The method used in this research is descriptive with quantitative approach with the intention to find correlation between independent variable with dependent variable by using statistic formula that is examining coordination relation to safety, health and work welfare and also relation of safety, health and work welfare to work productivity. While the statistical formula used to test the hypothesis is Multiple Linear Regression Analysis. Population in this research is 45 employeesof CV. Venus Inti Perkasa. The results of the study prove that: (1) there is a significant influence between the coordination of work safety that also affect work productivity. This is evidenced by the value of t-count> t-table (4.802> 2.01669). (2) The results also show that there is a significant influence between the coordination of occupational health which also affect work productivity. This is evidenced by the value of t-count> t-table (3.950> 2.01669). (3) The results showed that there is a significant influence between the coordination of work welfare that also affect work productivity. This is evidenced by t-count> t-table (3.476> 2.01669). (4) The result of research indicates that there are significant influence on K3 (Safety, Health and Welfare) variable on employee productivity as proved by Thitung (11,787)> T table (2.01669). And (5) The results showed that there is a significant influence between Coordination that is not directly to the Productivity Employee Performance through K3 with the result Fcount 4.906> Ftable 3.22.